Thank you next unpacking cancel culture on Twitter, as practiced by college students from the University of the Philippines Diliman - Vasquez, Pauline Bayani; Claudio, Ma. Ivy A. (Quezon City College of Mass Communication, University of the Philippines, 2023)
As cancel culture became more popularized on social media, the online public became more unforgiving—one mistake and it is thank you, next. However, despite growing interest in new media studies, knowledge about it remained "surface level at best" (Haskell, 2021, p. 102).

Thus, this study offered a new perspective to the discourse by employing Theodore Schatzki's (2001) practice theory and Henry Jenkins' (2009; 2015) participatory culture—deemed compatible by definition—in its framework.

It unpacked cancel culture as a practice through the lived experiences of three (3) college students from the University of the Philippines Diliman, as narrated in two (2) one-on-one semi-structured interviews. Using Colaizzi's (1978) descriptive phenomenological method and Braun and Clarke's (2006) theoretical thematic analysis, it was found that the practical understandings, rules, and teleoaffective structure held by the respondents could be traced back to their social interactions, indicating that even online practices—such as cancel culture—could not be carried out entirely independently from everyday life, whether online or offline. Additionally, it was the respondents' common goal of holding someone accountable which united them in their practices despite their different upbringings.
Kasabay ng pagsikat ng cancel culture sa social media. naging mas hindi mapagpatawad ang madla—isang pagkakamali lamang at ang katapat nito ay "thank you next.' Subalit. sa kabila ng lumalagong interes dito sa new media studies, ang kaalaman tungkol dito ay nananatiling mababaw o surface level lamang (Haskell. 2021).

Samakatuwid, ang pag-aaral na ito ay nagbigay ng panibagong perspektiba sa diskurso sa pamatnagitan ng paggamit ng practice theory ni Theodore Schatzki (2001) at participatory culture ni Henry Jenkins (2009; 2015)—na itinuturing magkasundo ang depinisyon—sa balangkas nito.

Inintindi ng pag-aaral na ito ang cancel culture bilang isang gawi (practice) pamamagitan ng lived experiences na isinalaysay ng tatlong (3) piling estudyante mula sa Unibersidad ng Pilipinas-Diliman sa loob ng dalawang (2) one-on-one semi-structure interviews. Gamit ang descriptive phenomenological method ni Colaizzi (1978) theoretical thematic analysis nina Braun at Clarke (2006), napag-alamang ang pinanghahawakang mga practical understandings, rules, and teleoaffective structure ay mula sa kanilang sosyal na interaksyon. na nagpapahiwatig na kahit ang mga gassing online—tulad ng cancel culture—ay hindi kayang ihiwalay sa pang-araw-araw na buhay mapa-online man o offline. Dagdag pa rito, ang kanilang iisang layunin na humingi ng pananagutan ang nagbuklod sa kanila sa kabila ng kanilang ibang kinalakihan.
Vita.
Thesis
Includes bibliographical references (pages 85-90) and appendices (pages 91-99).
Keywords: Online social network -- Philippines; Cancel culture -- Philippines; Social media -- Philippines